1999
DOI: 10.1006/dbio.1999.9489
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Targeting and Pathfinding Errors of Retinal Axons Following Overexpression of EphrinA Ligands on Retinal Ganglion Cell Axons

Abstract: In the retinotectal projection, the Eph receptor tyrosine kinase ligands ephrinA2 and ephrinA5 are differentially expressed not only in the tectum, but also in a high-nasal-to-low-temporal pattern in the retina. Recently, we have shown that retrovirally driven overexpression of ephrinA2 on retinal axons leads to topographic targeting errors of temporal axons in that they overshoot their normal termination zones in the rostral tectum and project onto the mid- and caudal tectum. The behavior of nasal axons, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…Novel experimental results by Hornberger et al (1999) and Du« tting et al (1999), however, indicate an additional function of the guidance ligands. These showed that the ligands are expressed not only on the tectum, but also on retinal ganglion cells.…”
Section: Models Based On the Imprint-matching Concept Of Retinotectalmentioning
confidence: 95%
“…Novel experimental results by Hornberger et al (1999) and Du« tting et al (1999), however, indicate an additional function of the guidance ligands. These showed that the ligands are expressed not only on the tectum, but also on retinal ganglion cells.…”
Section: Models Based On the Imprint-matching Concept Of Retinotectalmentioning
confidence: 95%
“…The ligands of EphA receptors, ephrin-A2 and ephrin-A5, have been reported to be expressed in the nasal retina and control the retinotectal projection along the A-P axis by modulating EphA receptor function (Dütting et al, 1999;Hornberger et al, 1999). Ephrin-A2, but not ephrin-A5, was found to be expressed with a V/N-high oblique-gradient at E8 (Fig.…”
Section: Oblique-gradient Molecules In the Retinamentioning
confidence: 99%
“…Complementary to the receptor gradient, the ligands ephrin-A2 and -A5 constitute an anterior (low) to posterior (high) gradient in the optic tectum (9,(11)(12)(13). Disruption of the ligand gradient by retrovirus-mediated gene expression or by gene manipulation techniques resulted in mistargeting of retinal axons (3,(14)(15)(16)(17)(18)(19). These analyses suggest critical roles of ephrins and their receptors in regulating development of retinotectal topographic map.…”
mentioning
confidence: 91%